Investigation of Electrochemical and Morphological Properties of Mixed Matrix Polysulfone-Silica Anion Exchange Membrane - Khoiruddin, Khoiruddin; Wenten, I Gede (ITB Journal Publisher, LPPM ITB, 2016)
Mixed matrix anion exchange membranes (AEMs) were synthesized using dry-wet phase inversion. The casting solutions were prepared by dispersing finely ground anion-exchange resin particles in N,N-dimethylacetamide (DMAc) solutions of polysulfone (PSf). Subsequently, nanosilica particles were introduced into the membranes. The results show that evaporation time (tev) and solution composition contributed to membrane properties formation. A longer tev produces membranes with reduced void fraction inside the membranes, thus the amount of water adsorbed and membrane conductivity are reduced. Meanwhile, the permselectivity was improved by increasing tev, since a longer tev produces membranes with a narrower channel for ion migration and more effective Donnan exclusion. The incorporation of 0.5 %-wt nanosilica particles into the polymer matrix led to conductivity improvement (from 2.27 to 3.41 mS.cm-1). This may be associated with additional pathway formation by hydroxyl groups on the silica surface that entraps water and assists ion migration. However, at further silica loading (1.0 and 1.5 %-wt), these properties decreased (to 1.9 and 1.4 mS.cm-1 respectively), which attributed to inaccessibility of ion-exchange functional groups due to membrane compactness. It was found from the results that nanosilica contributes to membrane formation (increases casting solution viscosity then reduces void fraction) and membrane functional group addition (provides hydroxyl groups).